Good food, strong communities : promoting social justice through local and regional food systems - Ventura, Steve, 1955-; Bailkey, Martin (University of Iowa Press, 2017)
Good Food, Strong Communities shares ideas and stories about efforts to improve food security in large urban areas of the United States by strengthening community food systems. It draws on five years of collaboration between a research team composed of the University of Wisconsin, Growing Power, the Michael Fields Agricultural Institute, and more than thirty organizations on the front lines of this work. Here, activists and scholars talk about what's working and what still needs to be done to ensure that everyone has access to readily available, affordable, appropriate, and acceptable food. This book helps readers understand how a food system functions and how individual and community initiatives can lessen the problems associated with an industrialized food system.